RESPIRATORY MUSCLE TRAINING IN SPORTS AND REHABILITATION: A LITERATURE REVIEW - Łubianka, Martyna; Słyś, Wiktor (International Journal of Innovative Technologies in Social Science, 2026)
Background. Historically, the respiratory system was viewed as an overbuilt apparatus that rarely limited human performance or daily function. However, contemporary research establishes that the respiratory system can become a profound limiting factor under physiological stress, high-intensity exercise and chronic disease. Respiratory muscle training (RMT) represents a targeted modality to enhance the strength and endurance of the respiratory musculature. Aim. To integrate and evaluate the human evidence surrounding the effects of respiratory muscle training (RMT) on athletic performance, clinical rehabilitation, symptom control, and return to physical activity, contextualizing the physiological mechanisms and specific training protocols. Material and methods. A review of the literature was conducted focusing on the clinical and athletic applications of RMT, primarily inspiratory muscle training (IMT) and expiratory muscle training (EMT), utilizing resistive loading, pressure threshold loading, and normocapnic hyperpnea modalities. Results. Several studies indicate that RMT may induce structural adaptations of the diaphragm as well as neural changes related to improved motor unit recruitment. In clinical populations (CHF, COPD, Asthma, Stroke, SCI, post-COVID-19 syndrome), RMT significantly increases maximal inspiratory pressure (MIP), reduces the Borg dyspnea index, and improves functional mobility (e.g., 6MWT distance). In athletic populations, RMT attenuates the respiratory metaboreflex, preserves peripheral locomotor blood flow and enhances specific field assessments like Repeated Sprint Ability (RSA) and Yo-Yo Intermittent Recovery Test (YYT). Conclusions. RMT is an effective, well-supported intervention that strengthens the diaphragm, reduces dyspnea, and improves exercise capacity across clinical and athletic populations. Outcomes depend on adherence to progressive overload and individualized protocols.